2011
DOI: 10.7468/jksmeb.2011.18.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Cloz-Covers of Tychonoff Spaces

Abstract: Abstract. In this paper, we construct a cover (L(X), c X ) of a space X such that for any cloz-coverUsing this, we show that every Tychonoff space X has a minimal cloz-cover (E cc (X), z X ) and that for a strongly zero-dimensional space X, βE cc (X) = E cc (βX) if and only if Ecc(X) is z # -embedded in Ecc(βX).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…proved similar results for the category of Hausdorff spaces and perfect continuous maps (the category of regular spaces and perfect continuous maps, resp.). To generalize extremally disconnected spaces, basically disconnected spaces, quasi-F spaces and cloz-spaces have been introduced and their minimal covers have been studied by various authors [3], [6], [7], [8], [10], [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…proved similar results for the category of Hausdorff spaces and perfect continuous maps (the category of regular spaces and perfect continuous maps, resp.). To generalize extremally disconnected spaces, basically disconnected spaces, quasi-F spaces and cloz-spaces have been introduced and their minimal covers have been studied by various authors [3], [6], [7], [8], [10], [13] .…”
Section: Introductionmentioning
confidence: 99%
“…In [10], it is shown that for a weakly Lindelöf space X, βE cc (X) = E cc (βX) and every spaces has a minimal cloz-cover.…”
Section: Introductionmentioning
confidence: 99%
“…Then βE cc (X) = E cc (βX) if and only if E cc (X) is z # -embedded in E cc (βX), that is, for any A ∈ Z(E cc (X)) # , there is a B ∈ Z(E cc (βX)) # such that A = B∩E cc (X). Morever, if βE cc (X) = E cc (βX), then z X : E cc (X) −→ X is z # -irreducible, that is, z X (Z(E cc (X)) # ) ⊆ Z(X) # ( [7]). For any strongly zero-dimensional space X, S(G(βX)) and βX are zero-dimensional space and hence E cc (βX) is a zero-dimensional space.…”
Section: Minimal Cloz-covers and Boolean Algebrasmentioning
confidence: 99%
“…Then E cc (X) is the subspace [6]). Moreover, it was shown that every space has a minimal cloz-cover( [7]). …”
Section: Minimal Cloz-covers and Boolean Algebrasmentioning
confidence: 99%
See 1 more Smart Citation